FORMULATION AND EVALUATION OF VALSARTAN FAST DISINTEGRATING TABLETS BY VACUUM DRYING TECHNIQUE - P, Durga Bhavani; NG, RAGHAVENDRA RAO (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The main objective present research work an attempt has been made to prepare fast dissolving tablets of Valsartan by using vacuum drying technique. Camphor, Urea and Menthol are used as a sublimating agent. Valsartan is an oral antihypertensive agent, with problems of variable bioavailability and bioequivalence related to its poor water solubility. Valsartan is an angiotensin II type 1 receptor antagonist indicated in the treatment of hypertension. Methods: The prepared tablets Valsartan fast dissolving tablets were evaluated for various parameters like weight variation, hardness, friability, disintegration time, drug content, water absorption ratio, wetting time, in- vitro drug release, FTIR, DSC studies and short term stability studies. The blend was examined for the pre-compressional and post-compressional parameter. Results and Discussions: The values of pre-compression parameters evaluated were within prescribed limits and indicated good free flowing property. All the post-compressional parameter are evaluated were prescribed limits and results were within IP acceptable limits. Based on the invitro disintegration time and dissolution studies formulations SC2 and SC3 were found to be promising and showed a disintegration time of 24 sec and 16 sec respectively. Formulation SC3 containing camphor showed highest drug release 99.4% within 10 min. IR spectral analysis and DSC study showed that there was no drug interaction with formulation additives of the tablet as there is no variation and shift in the position of characteristic absorption bands it can be justified there is no interaction between drug and polymer. Short term stability studies on the formulations indicated that there are no significant change in hardness, friability, drug content and in-vitro drug release (p<0.05). Conclusion: The results concluded that fast dissolving tablets of Valsartan showing enhanced dissolution may lead to improved bioavailability and effective therapy by using sublimation method. Keywords: Fast dissolving tablet, Valsartan, Crospovidone, Camphor, Urea, Disintegration time.